Vineyard Clusters Monitored by Means of Litterbag-NIRS and Foliar-NIRS Spectroscopic Methods - Cugnetto Alberto; Lajolo Luciano; Vitaloni Giovanni; Sarasso Giuseppe; Corrado Borgogno Mondino Enrico; Nuti Marco; Giovannetti Giusto; Masoero Giorgio (Journal of Agronomy Research, 2021)
There is currently a lack of rapid indirect analysis methods for the assessment of the effects of soil microbiota on vine production. Fifteen clusters of two Nebbiolo and Erbaluce varieties were identified in five vineyards belonging to a cooperative of winemakers in North West Italy, according to the differences in the NDVI index, as monitored by the Crop Monitoring OES system. The vineyards were surveyed in 2019 and the experimental monitoring of 75 vines was conducted in 2020. The first indirect method (Litterbag-NIRS) involved examining hay litterbags with a smart SCiOTM device. The average litterbag-NIR spectra of the clusters, as far as the yield is concerned, were closely fitted with the measured production yield, with an R2 cross-validated value of 0.91 in the Nebbiolo vines and 0.67 in the Erbaluce vines. The results in yield were accounted for by considering a few dominant variables in both vines, namely the microbic respiration of the soil and the crude protein of the litterbag (positive), opposed to the soil NO3–N and litterbag ADF (negative). The pruning wood was also closely correlated to the litterbag spectra. A second rapid method, foliar pH coupled with the NIR spectroscopy of the leaves, was then performed. The overall results predicted from the foliar NIRS were 0.73 for yield and 0.79 for the Canopy Cover. However, the most interesting result concerned the yield regressions on the foliar pH, which were clearly negative in both vines and of a similar amount: -5.15 kg/pH in Nebbiolo (R2 0.68) and -5.63 kg/pH (R2 0.23) in Erbaluce. Litterbag-NIRS, which shows a high predictive capacity, and foliar pH - with or without foliar-NIRS - are indirect and frugal methods that can be recommended for a rational assessment of the microbial soil fertility of vineyards.
Keywords: Vine